1985
DOI: 10.2118/12387-pa
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Considerations in Malaysia's First Waterflood

Abstract: Summary Malaysia's first waterflood, a seawater injection system, was placed in service in the Tapis field in 1982. This paper outlines the design basis and describes the system. Then water quality during and after startup and the formulation of a water quality guide using Millipore membrane filtration tests are discussed. The experience gained and data presented can be applied to current and future waterfloods. Introduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Several other models exist to describe fracturing, injectivity decline, formation damage, particulate mechanics and this have been published elsewhere (AbouSayed et al 2005(AbouSayed et al , 2007Al-Abduwani 2005;Bedrikovetsky et al 2007;Chang 1985;Clifford et al 1991;Davidson 1979;De Zwart 2007;Dong et al 2010;Donaldson et al 1977;Doresa et al 2012;Farajzadeh 2002;Faruk 2010;Folarin et al 2013;Furtado et al 2005;Gong et al 2013;Greenhill 2002;Guedes et al 2006;Hustedt et al 2006;Iwasaki 1937;Khatib 2007;Khodaverdian et al 2009;Lawal and Vesovic 2010;Lawal et al 2011;Li et al 2011Li et al , 2012Ojukwu and van den Hoek 2004;Sahni and Kovacevich 2007;Shuler and Subcaskey 1997;Todd 1979; Van den Hoek et al 1996;Wang and Le 2008;Wang et al 2011;Sharma et al 2000;Yerramilli et al 2013;Zeinijahromi et al 2011;Zhang et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Several other models exist to describe fracturing, injectivity decline, formation damage, particulate mechanics and this have been published elsewhere (AbouSayed et al 2005(AbouSayed et al , 2007Al-Abduwani 2005;Bedrikovetsky et al 2007;Chang 1985;Clifford et al 1991;Davidson 1979;De Zwart 2007;Dong et al 2010;Donaldson et al 1977;Doresa et al 2012;Farajzadeh 2002;Faruk 2010;Folarin et al 2013;Furtado et al 2005;Gong et al 2013;Greenhill 2002;Guedes et al 2006;Hustedt et al 2006;Iwasaki 1937;Khatib 2007;Khodaverdian et al 2009;Lawal and Vesovic 2010;Lawal et al 2011;Li et al 2011Li et al , 2012Ojukwu and van den Hoek 2004;Sahni and Kovacevich 2007;Shuler and Subcaskey 1997;Todd 1979; Van den Hoek et al 1996;Wang and Le 2008;Wang et al 2011;Sharma et al 2000;Yerramilli et al 2013;Zeinijahromi et al 2011;Zhang et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In theory, efficiency and sustainability of the PWRI were progressed by considering injectivity decline as an outcome of momentum and particulate transport phenomena in porous media (Mendez 1999). There are other model and studies reported in technical literatures by previous researchers that focused on the filtration coefficient as the sole determinant of injectivity decline and fracturing (Abou-Sayed et al 2007;Ajay andSharman 2007, Al-Abduwani et al 2001;Altoef et al 2004;Chang 1985;Clifford et al 1991;Donaldson et al 1977;Doresa et al 2012;Folarin et al 2013;Gong et al 2013;Hustedt et al 2006). None of these models hinted on possible geochemical reaction of produced water heavy metals and aquifer water constituents and effect of geochemical reaction, the focus of this research study.…”
Section: Introductionmentioning
confidence: 99%